Antidiabetic and Antioxidant Properties of Sea Urchin Echinometra mathaei from the Persian Gulf - Soolmaz Soleimani; Elham Pirmoradloo; Fatemeh Farmani; Soheila Moein; Morteza Yousefzadi (Journal of Kerman University of Medical Sciences, 2021)
Background: The aim of the present study was to evaluate the inhibition of α-glucosidase and antioxidant properties of different tissues of sea urchin Echinometra mathaei. Methods: α-glucosidase inhibition was determined using p-Nitrophenyl-a-D-glucopyranoside as a substrate, and the antioxidant properties were evaluated by 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS),1,1-diphenyl-2-picrylhydrazyl (DPPH), and nitric oxide radicals scavenging. Also, antioxidant potential was evaluated by the ferric reducing antioxidant power (FRAP) method. Results: Among the studied tissues, the highest α-glucosidase inhibition was revealed by the ethyl acetate extract of the shell and Aristotle’s lantern (IC50 = 3.7 and 4 mg/mL, respectively). Shell had the highest ABTS (IC50 = 183) and DPPH (IC50 = 208 μg/mL) radicals scavenging, respectively. And, gonad had the highest antioxidant potential by the FRAP method (1140 μg ASA/mg) and NO radical scavenging (70.68%), respectively. Conclusion: Antidiabetic potentials of the ethyl acetate extracts of sea urchin tissues suggest that these extracts can be used as antidiabetic drugs.